2018
DOI: 10.1016/j.jmb.2018.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Network Analysis of UBE3A/E6AP-Associated Proteins Provides Connections to Several Distinct Cellular Processes

Abstract: Perturbations in activity and dosage of the UBE3A ubiquitin-ligase have been linked to Angelman syndrome and autism spectrum disorders. UBE3A was initially identified as the cellular protein hijacked by the human papillomavirus E6 protein to mediate the ubiquitylation of p53, a function critical to the oncogenic potential of these viruses. Although a number of substrates have been identified, the normal cellular functions and pathways affected by UBE3A are largely unknown. Previously, we showed that UBE3A asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 188 publications
(237 reference statements)
0
31
0
Order By: Relevance
“…The 26S proteasome is one of the major cellular complexes interacting with UBE3A (21)(22)(23)(24)(25)(26)(27)(28)(29). Although immunoprecipitation and MS cannot distinguish which specific protein subunit within the 26S proteasome directly binds UBE3A, PSMD4 was the only proteasomal subunit identified as a direct UBE3Abinding partner in a yeast two-hybrid screen we recently reported, suggesting that PSMD4 likely bridges the interaction of UBE3A with the 26S proteasome (24).…”
Section: The 26s Proteasome Binds To the N Terminus Of Ube3amentioning
confidence: 85%
See 2 more Smart Citations
“…The 26S proteasome is one of the major cellular complexes interacting with UBE3A (21)(22)(23)(24)(25)(26)(27)(28)(29). Although immunoprecipitation and MS cannot distinguish which specific protein subunit within the 26S proteasome directly binds UBE3A, PSMD4 was the only proteasomal subunit identified as a direct UBE3Abinding partner in a yeast two-hybrid screen we recently reported, suggesting that PSMD4 likely bridges the interaction of UBE3A with the 26S proteasome (24).…”
Section: The 26s Proteasome Binds To the N Terminus Of Ube3amentioning
confidence: 85%
“…We recently identified PSMD4 as a UBE3A-interacting protein in a yeast two-hybrid screen, indicating that PSMD4 is likely a direct interaction partner of UBE3A (24). To examine this possibility further, we tested binding of the isolated UBE3A AZUL domain to PSMD4 with recombinant proteins expressed in bacteria.…”
Section: Characterizing the Interaction Of Ube3a/e6ap With Psmd4mentioning
confidence: 99%
See 1 more Smart Citation
“…E6AP is known to ubiquitinate and degrade wide range of proteins that include p53, PML, C/EBPα, MNT, G‐CSFR and others involved in various cellular functions . Dysregulation of E6AP expression and function has been associated with numerous diseases such as cervical carcinogenesis, Angelman syndrome and others . In a recent study E6AP was shown to act as a tumor suppressor in non‐small cell lung cancer by maintaining INK4/ARF expression levels .…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has illuminated diverse roles for UBE3A in neuronal and cellular functions. Proteomic analyses have suggested that UBE3A and its interacting proteins integrate several cellular processes including translation, intracellular trafficking, and cytoskeleton regulation, which are all necessary for neuronal function (8,9). In line with its role in neurodevelopmental disease, UBE3A has also been shown to be critical in synaptic formation and maintenance (1012).…”
Section: Introductionmentioning
confidence: 99%